Comparison and Correlation Analysis of Microbial Community Diversity and Flavor Compounds in Different Layers of Pit Mud for Luzhou-flavor Baijiu in Different Seasons - WANG Yiwen, TIAN Yaoyao, ZHANG Kefen, ZHANG Suyi, GAO Jie, TANG Hongjie, SONG Chuan, TANG Yu, SUN Mingjun, ZUO Yong, LI Qi (Shipin Kexue)
This study focused on the analysis of the microbial community structure and flavor substances of different layers of pit mud for Luzhou-flavor baijiu in spring and autumn using high-throughput sequencing and headspace solid-phase microextraction combined with gas chromatography-mass spectrometry (HS-SPME-GC-MS), and it also used Spearman correlation analysis to examine the correlation between dominant microbial genera and flavor compounds. The results showed that for each layer of pit mud, the diversity of both prokaryotes and eukaryotes was higher in autumn than in spring. In all samples, 21 prokaryotic phyla, 45 classes, 82 orders, 128 families and 241 genera were detected, including 7 dominant phyla and 43 dominant genera; 7 eukaryotic phyla, 19 classes, 33 orders, 81 families and 134 genera were detected, including 5 dominant phyla and 34 dominant genera. The types and relative contents of flavor compounds in pit mud were significantly different between different seasons and layers, with both the types and relative contents of flavor compounds being higher in the middle layer of pit mud in spring. The correlation analysis showed that Caproiciproducens and Aspergillus were correlated with the production of a variety of flavor compounds, and microorganisms that were positively correlated with the key flavor compounds caproic acid and ethyl caproate in pit mud significantly varied between different seasons and layers. These results revealed the microbial composition of the pit mud and the correlation with flavor compounds from the dimensions of time and space, and provided theoretical references for the excavation of aroma-producing microorganisms in the pit mud.